Inequality, transfers and growth: New evidence from the economic transition in Poland - Keane, M; Prasad, E (IZA Institute of Labor Economics, 2002)
This paper challenges the conventional wisdom that inequality in Poland increased markedly during the economic transition that began in 1989-90. Using micro data from the Household Budget Surveys, we find that, after a brief spike in 1989, income and consumption inequality actually declined to below pre-transition levels during 1990-92 and then increased gradually, rising only moderately above pre-transition levels by 1997. In sharp contrast, inequality in labor earnings increased markedly and consistently throughout the 1990-97 period. We find that social transfer mechanisms, including pensions, played an important role in mitigating increases in both overall inequality and poverty. We argue that, from a political economy perspective, transfer mechanisms were well-designed to reduce political resistance to market-oriented reforms in the early years of transition, paving the way for rapid growth. Finally, we provide cross-country evidence from the transition economies that is consistent with our interpretation of the Polish experience and is also consistent with recent work in growth theory which suggests that redistribution that reduces inequality can enhance growth.